Laksmi Pamuntjak's 'Amba' and re-membering fractured identities in Indonesia - Ahmad, Siti Nuraishah (Facutty Letters, Universitas Sanata Dharma, 2015)
The events of 30 September 1965 and its aftermath are a catastrophic chapter in the history of post-colonial Indonesia. Metaphors of loss, rupture, and, to borrow Max Lane’s term, “an unfinished nation” have since been used in writings about the systematic destruction of the left in Indonesia in 1965-66. These metaphors can also be extended to the identity construction of Indonesians, as portrayed in the novel Amba (2012) by Laksmi Pamuntjak. The novel’s protagonists represent Indonesians whose identities are fractured by the violence, trauma and alienation brought about by the purge of the PKI— both those who were directly affected by the events (Amba and Bhisma) and those who came after (Samuel and Srikandi). Their fractured identities need to be pieced back together through acts of re-membering and the search for truth and closure, however fragmented and incomplete these processes may be. Using theoretical approaches from trauma and memory studies, this paper examines the said characters and the journeys they undertake to recover a sense of selfhood that was broken or lost in or because of the events of 1965-66.